Research on using vegetable oil-ethanol mixture as fuel for diesel engine driving generator - Mai Nghia Duc; Duc Tuan Ho; Pham Trung Dinh (E3S Web of Conferences)
The demand for petroleum fuels for internal combustion engines, including diesel engines, is increasing, which increases pollution emissions from engine exhaust, negatively affecting the environment. In response to environmental protection requirements, many biofuels are produced and applied to engines to limit dependence on petroleum fuels and reduce toxic emissions because biofuels are environmentally friendly and renewable. However, the engine’s specific fuel consumption may increase due to the differences in combustion properties between vegetable oil and diesel fuel. This article used a mixture of vegetable oil (coconut oil) mixed with ethanol at different ratios and heated to reduce viscosity as fuel for a diesel engine. Experimental research results have shown that engines using a mixture of coconut oil and ethanol with a mixing ratio of 15% ethanol and heating the mixture to a temperature of about (60 - 65)0C have specific low fuel consumption, which reflects that the engine can use the above mixture as fuel, contributes to reducing pollution from exhaust gas and protecting the environment. Keywords. Diesel engine, vegetable oil, ethanol, viscosity, specific fuel consumption